Intensivierungspläne österreichischer MilchproduzentInnen angesichts der auslaufenden Milchquotenregelung 2015: Ein empirisches Modell zur Erklärung von Verhaltensintentionen; Intensification Plans of Austrian Farmers beyond Dairy Quotas - An Empirical Model to Explain Planned Behaviour - Manuela Larcher; Martin Schon̈hart; Erwin Schmid; Stefan Vogel (German Journal of Agricultural Economics (GJAE), 2015)
– This article analyses intensification plans of Austrian dairy farmers after the abolition of the EU milk quota regime in 2015. Binary logistic regression models have been developed using survey data (N = 455) on farmers' values, believes, expectations, and plans. The models are tested on its ability to predict intensification plans in dairy production. The results indicate that midterm plans are mainly determined by farmers' attitudes towards own behaviour as well as perceptions on behavioural control. Orientation towards farm enlargement and optimistic perceptions on management options after the abolition of the milk quota in 2015 are preconditions for intensification plans even if farm succession strategies are already settled and farm resource endowments are seen sufficient.
Keywords: 330